Inflammatory Myofibroblastic Tumor Involving the Pterygopalatine Fossa - Ribeiro, Andrea Campos de Oliveira; Joshi, Varsha M.; Funkhouser, William K.; Mukherji, Suresh K. (American Journal of Neuroradiology, 2001)
Summary: Inflammatory myofibroblastic tumors (IMT) comprise a rare group of lesions characterized histologically by acute and chronic inflammatory cells with a variable degree of fibrous stroma. Occurrence in the extracranial head and neck in children is unusual, and involvement in the pterygopalatine fossa has not, to our knowledge, been reported as occurring in this age group. We present the CT findings of an IMT of the pterygopalatine fossa in a 6-year-old female patient with a 2-week history of fever and a painless swelling of the left cheek. The diagnosis of IMT should be included in the differential diagnosis of a child presenting with an aggressive mass associated with systemic features such as fever, elevated sedimentation rate, and leukocytosis.